Usefulness of immunohistochemical staining for MUC5AC in differentiating primary pancreatic cancer from pancreatic metastasis of breast cancer. Issue 10 (6th June 2019) - Yamashita, Hiroki; Kurita, Akira; Azuma, Shunjiro; Kudo, Yasushi; Matsuzaki, Naomi; Yazumi, Shujiro
Abstract: Diagnosis of pancreatic ductal adenocarcinoma (PDAC) and its differentiation from metastases to the pancreas from other organs remains challenging. We report a case in which immunohistochemical staining for MUC5AC was useful in distinguishing primary pancreatic cancer from breast cancer metastasis. A 51‐year‐old Japanese woman who underwent curative resection of her breast cancer was referred to our hospital with a pancreatic head tumor. Although we surmised her pancreatic tumor to be metastatic breast cancer based on her past history and imaging studies, she was subsequently diagnosed with PDAC on the basis of immunohistochemical staining for MUC5AC using specimens obtained by endoscopic ultrasound‐fine‐needle aspiration. Thus, MUC5AC may be a useful diagnostic marker for discriminating PDAC from a secondary malignancy.